Carmen M. Palomo Pinel, ‘Nec inmerito paterfamilias dicitur’. El ‘pater-familias’ en el pensamiento de Lactancio, Dykinson, Madrid 2017, pp. 465, ISBN 978-84-914-8471-4 - Rodríguez González, Ana Mª (ΠΗΓΗ/FONS, 2020)
–